2000
DOI: 10.1146/annurev.biophys.29.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetically Controlled Microfluidic Analysis Systems

Abstract: Electrokinetic forces are emerging as a powerful means to drive microfluidic systems with flow channel cross-sectional dimensions in the tens of micrometers and flow rates in the nanoliter per second range. These systems provide many advantages such as improved analysis speed, improved reproducibility, greatly reduced reagent consumption, and the ability to perform multiple operations in an integrated fashion. Planar microfabrication methods are used to make these analysis chips in materials such as glass or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
145
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(145 citation statements)
references
References 88 publications
0
145
0
Order By: Relevance
“…If I f is known, u can be calculated using eqn. (3). The signal from the optical detector increases with the total photoemission from the measuring volume.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 2 more Smart Citations
“…If I f is known, u can be calculated using eqn. (3). The signal from the optical detector increases with the total photoemission from the measuring volume.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…(3) indicates that for a given system (dye, buffer, and laser beam property), I f increases with u. If I f is known, u can be calculated using eqn.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the main reason why they have attracted so much interest in recent years [1]. For pumping, electroosmotic flow (EOF) is usually the method of choice as it is rather easy to implement experimentally compared to pressure-driven flow [2][3][4][5]. However, the main weakness of EOF is the stability of the flow rate, and perhaps this is why capillary electrophoresis (CE) as a separation technique is not always as reproducible as required.…”
Section: Introductionmentioning
confidence: 99%
“…Bousse et al 18 suggested that analyzing one sample within 1 min, and a set of ten samples on one LabChip takes approximately 25-30 min. 18 The peak number, molecular weight ͑present as kDa͒, migration time ͑present as second͒, and protein content of these proteins are shown in Figs. 3 and …”
Section: B Comparison Of Glycoproteins By Labchip and Sds-pagementioning
confidence: 99%